The Effectiveness of the Combination of Bay Leaf Extract (Syzygium polyanthum) and Celery Leaf Extract (Apium graveolans L.) on Lowering Blood Sugar Level in Wistar Rats (Rattus norvegicus) - Laorenz, Diva Erita; Naldi, Yandri; Oktavrisa, Friska (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Diabetes mellitus is a metabolic disorder marked by high blood glucose levels. According to the WHO, approximately 422 million people worldwide were living with diabetes in 2023, with 1.5 million diabetes-related deaths reported annually. Based on the RISKESDAS data, the prevalence of diabetes in Indonesia was 8.5% in 2018, affecting approximately 20.4 million individuals, and the increase is closely linked to rising obesity rates. Diabetes treatment involves both medication and lifestyle changes. Indonesia has many herbal plants, such as bay and celery leaves, which contain bioactive compounds like flavonoids, alkaloids, saponins, and tannins believed to have antihyperglycemic properties. Aims: This study aimed to evaluate the effectiveness of the combination of bay leaf extract (Syzygium polyanthum) and celery leaf extracts (Apium graveolans L.) against lowering blood sugar levels in white male Wistar rats (Rattus norvegicus). Methods: This research is an experimental study using a pre- and post-test control group design. A total of 25 male Wistar white rats (Rattus norvegicus) were induced with alloxan and then divided into five groups: Group 1 (G1) as the negative control; Group 2 (G2) as the positive control, treated with the drug glibenclamide; Group 3 (G3) received bay leaf extract at a dose of 300 mg/kgBW; Group 4 (G4) received celery leaf extract at a dose of 300 mg/kgBW; and Group 5 (G5) received a combination of bay leaf and celery leaf extracts at a dose of 300 mg/kgBW. The post-test was conducted twice : Post-test 1 was carried out 60th minutes after treatment, and Post-test 2 was conducted 120th minutes after treatment. Blood glucose levels were measured using a glucometer. Results: At 60th minutes post-treatment, blood sugar levels decreased by 40 mg/dL in G1, 100 mg/dL in G2, 44 mg/dL in G3, 57.4 mg/dL in G4, and 70.8 mg/dL in G5. At 120th minutes, the decreases were 45 mg/dL (G1), 104.6 mg/dL (G2), 49.2 mg/dL (G3), 62 mg/dL (G4), and 77.6 mg/dL (G5). The Post Hoc LSD test showed a statistically significant average decrease of 5 mg/dL between post-test 1 and post-test 2 (p < 0.001). Conclusion: The combination of bay leaf extract and celery leaf extract at a dose of 300 mg/kgBW is most effective in reducing blood glucose levels in hyperglycemic Wistar rats.